ANALISIS KESESUAIAN SKL, KI, KD, DAN INDIKATOR KURIKULUM PAI: ANALISIS KESESUAIAN SKL, KI, KD, DAN INDIKATOR KURIKULUM PAI - Utari, Anggie Sri; Syahputra, Tri Abdi; Halimah, Siti (Al-Ihda' : Jurnal Pendidikan dan Pemikiran, 2024)
ABSTRACT A thorough analysis of the alignment between SKL, KI, KD, and curriculum indicators of Islamic Education (PAI) is crucial to ensure that the curriculum developed is truly relevant to the needs of students and can significantly contribute to character building and a good understanding of Islam. This study aims to analyze the alignment between Graduate Competency Standards (SKL), Core Competencies (KI), Basic Competencies (KD), and indicators in the Islamic Education Curriculum (PAI). The alignment between these elements is a critical aspect in ensuring the effectiveness of the learning process and the achievement of the desired educational goals. The research method used is literature study with a descriptive qualitative approach. The results indicate that, in general, there is good alignment between SKL, KI, KD, and indicators; however, some discrepancies were found that could affect the achievement of student competencies. Some KD do not fully reflect the competencies expected in the SKL, and some indicators do not clearly measure the achievement of the set KD. These findings provide recommendations for improvements in the development and implementation of the PAI curriculum to be more integrated and consistent in achieving educational goals. Keywords : Curriculum Alignment, SKL, KI, KD, Indicators, Islamic Education